DNA extraction technique for different rice varieties grown in Sri Lanka - Kapilan, Ranganathan (International Journal of Applied Sciences and Biotechnology, 2015)
Extraction of DNA is very important nowadays in bio-molecular researches. Extracted DNA should be purified and the quality of DNA should also be very high. The objective of the study was to develop a simple efficient method to isolate DNA from the rice varieties in an open laboratory environment, and to eliminate the usage of expensive chemicals and tools. The DNA extraction methods developed by the DNeasy plant kit method supplied by QIAGEN, Cheng et al., Doyle et al. and Michiels et al. were applied to five different rice varieties grown in different parts of Sri Lanka. Based on the quantity and quality of the extracted DNA tested by measuring the absorbance of DNA at 260 nm using Nanodrop® ND-1000 spectrophotometer and measuring the ratio of A260 / A280 and gel running on agarose, the efficiency of the extraction method chosen varied among rice varieties. Among the methods used, the methods introduced by DNeasy plant kit method supplied by QIAGEN and Cheng et al, yielded good and amplifiable quality DNA with satisfactory concentration for all the rice varieties tested. Therefore the modified method of Cheng et al, 1987 could be used to extract DNA from rice varieties instead of the commercially available expensive and hazardous DNeasy plant kit method supplied by QIAGEN. Int J Appl Sci Biotechnol, Vol 3(3): 398-401